Update on diagnostic and management recommendations in paediatrics - Wąsowska-Królikowska, Krystyna; Toporowska-Kowalska, Ewa (Przewodnik Lekarza/Guide for GPs, 2008)
The paper summarizes the newest guidelines for vaccination and nutrition of healthy children. The most important modification of the vaccination schedule is the recommendation for mandatory vaccination against Haemophilus influenzae in infants. The main changes in infants’ nutrition include: earlier introduction of some complementary products – gluten (5th-6th month) and fish (7th month) – and postponement of the use of starting infant formula as the sole source of nutrition until 6 months of life. The new algorithms for treatment and management of cows’ milk protein allergy in breast and formula fed infants as well as the Global Initiative for Asthma 2006 (GINA 2006) update of asthma classification and treatment guidelines in young children are also discussed.